2021
DOI: 10.3389/fmed.2021.715640
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Multispectral Refraction Topography and Autorefractometer in Young Adults

Abstract: Purpose: Purpose of this study is to evaluate the measuring consistency of central refraction between multispectral refraction topography (MRT) and autorefractometry.Methods: This was a descriptive cross-sectional study including subjects in Sun Yat-sen Memorial Hospital from September 1, 2020, to December 31, 2020, ages 20 to 35 years with a best corrected visual acuity of 20/20 or better. All patients underwent cycloplegia, and the refractive status was estimated with autorefractometer, experienced optometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This may be due to the fact that the SR could measure the exact macular refractive error and could consider the posterior retina as a sphere although its actual shape is ellipse. Liao et al ( 25 ) have reported that the 95% LoA between MRT and autorefractometer ranged from −1.43 to 1.83 D. Similarly, we found that the same conclusion and the 95% interval of LoA was narrower. The MRT measurement in the peripheral retina may increase the difference compared with central retina, but it would still maintain the reliability.…”
Section: Discussionsupporting
confidence: 85%
“…This may be due to the fact that the SR could measure the exact macular refractive error and could consider the posterior retina as a sphere although its actual shape is ellipse. Liao et al ( 25 ) have reported that the 95% LoA between MRT and autorefractometer ranged from −1.43 to 1.83 D. Similarly, we found that the same conclusion and the 95% interval of LoA was narrower. The MRT measurement in the peripheral retina may increase the difference compared with central retina, but it would still maintain the reliability.…”
Section: Discussionsupporting
confidence: 85%
“…The BCVA is determined by objective refraction, such as via retinoscope or auto-refractometer, and subjective refraction. The auto-refractometric exam is rapid and provides fewer deviations than the subjective method with normal BCVA [ 31 , 32 ]. However, in diseased eyes, such as those with keratoconus or cataracts, there are high errors of auto-refractometric readings or even no readings.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al 17 noted that due to its ability to measure a large area of the peripheral retina, MRT is a preferred choice for examining the effect of optical treatments on peripheral refraction. Furthermore, Liao et al 18 described a high level of agreement between measurements of central refraction obtained using autorefractometry, subjective refraction by experienced optometrists and MRT.…”
Section: Introductionmentioning
confidence: 99%